DAMAGE PROCESS OF INTACT GRANITE UNDER UNIAXIAL COMPRESSION: MICROSCOPIC OBSERVATIONS AND CONTACT STRESS ANALYSIS OF GRAINS - Lee S.; Kim M.; Park Ja.; Park Ch.; Kang M.; Jeong G. (My University, 2006)
Understanding the damage mechanism in materials is one of the very important subjects in the science and engineering field. The microstructural change, microcracking, which causes material strength deterioration, is usually termed as damage. We observed micro-damage localization and propagation, in a coarse-grained granite specimen under uniaxial compressive stress to better understand the fundamental problems of the true damage process at a micro to macro scale. With the use of an experimental system, the continuous observation of the damage process also enabled us to clarify micro-damage in great detail. The results indicate that the mechanisms of micro-damage initiation in a granite specimen under uniaxial compressive stress may be separated into two cases; the first in which two grains, such as quartz and feld-spar, contact each other in the same direction as the axial stress, and the second in which a biotite grain inclined to the axial stress direction is contained within a feldspar grain. The damage is strongly localized for both cases and some shear zones are found in the specimens.
Keywords: GRANITE; UNIAXIAL COMPRESSIVE STRESS; MICRO-DAMAGE LOCALIZATION; DAMAGE MECHANISM